PEMBERIAN REWARD DALAM PEMBELAJARAN UNTUK MENINGKATKAN KEAKTIFAN BELAJAR ANAK USIA DINI: STUDI KUALITATIF DESKRIPTIF - Usman, A'zhami Alim; Rohmah, Lailatu (STKIP Persada Khatulistiwa Sintang, 2024)
This study aims to explore the provision of rewards in learning as an effort to increase early childhood learning activity. In particular, this study examines the efforts made by teachers in giving rewards through praise, awards, gifts, and signs of respect. The research used descriptive qualitative data collection through documentation, documentation, and structured and free interviews with four teachers. The collected data was analyzed using the Miles and Huberman model, which included three stages: data condensation, data presentation, and conclusion drawing. The results of the study show that various forms of rewards significantly increase children's learning activity. Praise and rewards provide a valuable sense of recognition to increase children's motivation and confidence. Simple gifts, such as snacks and stationery, create a fun learning atmosphere, while signs of respect, such as verbal acknowledgments and claps, reinforce the child's social engagement. This study concludes that the application of various reward strategies is effective in creating a conducive learning environment, encouraging children to participate more actively in the learning process. This finding is expected to be a reference for educators in designing innovative and responsive learning methods to children's needs.